The Effect Of Service Quality And Relationships On Customer Satisfaction Has An Impact On Customer Loyalty Of Self-Service Petrol Stations In Bekasi During The Covid-19 Pandemic - Tika Oktavia Samosir (Journal of Social Research, 2024)
This study aims to analyze the effect of tangible, reliability, assurance, responsiveness, empathy on customer satisfaction as well as the effect of relationship and customer satisfaction on customer loyalty of gas stations self-service during the covid 19 pandemic. The method used in this study uses quantitative methods. Data were collected through questionnaires distributed online. Respondents from this study were customers of gas stations self-service in Bekasi, amounting to 150 samples. The analysis technique uses the Structural Equation Model (SEM) with SPSS v13 and AMOS v20 tools. The results showed that the variables of reliability, assurance and responsiveness had an effect on customer satisfaction with gas stations, self-service but variables had tangible and empathy no effect on customer satisfaction, while the variables of customer satisfaction and relationship had an effect on customer loyalty with a system self-service.